(untitled) (Acta Horti Botanici Bucurestiensis, 2024)
Characterised by numerous microclimates that are present from the plain area and up to the alpine region, the territory of Oltenia previously offered and still manages to offer surprises from a floristic point of view, as well as from other perspectives. The recent climate changes have altered the typical habitats of some plants, resulting in their discovery in areas where, according to the data in the specialized literature, were not previously known to exist. Among the many species of Poaceae that are present in the spontaneous flora of Oltenia, there are certain species of sozological and phytogeographical interest. This is also the case with the species presented in the current paper, i.e. Polypogon monspeliensis (L.) Desf. Polypogon monspeliensis (L.) Desf. is an Atlantic-Mediterranean coastal species, found especially on the western and southern European coastal sands. It is native to northern Africa, southern and western Europe, western and northern Asia, Japan and the Indian subcontinent (India, Nepal, Pakistan, and Sri Lanka). The species has been widely naturalized in southern and eastern Australia, in South Africa, New Zealand, Canada, the USA, Central and South America, as well as in Hawaii. In Romania, it is known from the south-eastern part of the country: Tulcea and Constanța counties. In Poiana Brașov and Vaideeni (Vâlcea County), the species is mentioned as an adventive plant. The present paper contributes with information regarding the chorology and ecology of this species.